The European Union As A Global Economic Power - Mucha-Leszko, Bogumiła; Twarowska, Katarzyna (Comparative Economic Research. Central and Eastern Europe, 2016)
The aim of this study is to evaluate the EU economic position in 1995–2014 as well as the prospective growth potential in the global dimension up to 2025. The subject of the research is real and projected data including: GDP growth rate, main growth factors (labour, labour productivity and Total Factor Productivity), and their input to GDP growth, as well as data showing public debts and budget deficits. The analysis was conducted for the years 1995–2014 and 2015–2025. The authors' basic conclusions are: 1) the technological and economic gap between the European Union and the United States has been deepening; 2) the increasing polarisation of world economic powers and low GDP growth in the European Union limit the EU’s chances of maintaining the position as the second centre in the world economy; 3) improving the situation in public finances in the European Union as compared to the US is a factor which could raise GDP growth rates in European countries, however, there are countries whose future is in doubt due to the dramatically poor state of public finances, such as Greece, Italy, Portugal or Ireland; 4) economic growth forecasts indicate a deepening of the economic gap between the largest EU countries and the US.